The Role of Macrophages in the Pathogenesis of Celiac Disease - A. I. Khavkin; E. V. Loshkova; E. I. Kondratieva; N. S. Shapovalova; I. R. Grishkevich; I. V. Doroshenko; G. N. Yankina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present data on the involvement of macrophages in the pathogenesis of celiac disease and the development of possible treatment methods for this disease aimed at changing the function of macrophages.Key points. Celiac disease is an autoimmune disease with a characteristic serological (antibodies to tissue transglutaminase, endomysium, deamidated gliadin peptides) and histological profile (inflammatory infiltration of the villous epithelium by lymphocytes and their atrophy, crypt hyperplasia) caused by gluten consumption in genetically predisposed individuals. Macrophages, as key cells that provide a link between innate and adaptive immunity, are of significant importance in the pathogenesis of celiac disease. Gliadin peptides stimulate the activation of macrophages according to the proinflammatory phenotype with the production of cytokines, which causes the immune response of T-helpers 1 and T-helpers 17. The result of these processes is the development of an inflammatory reaction and damage to the intestinal mucosa due to the production of matrix metalloproteinases and reactive oxygen species by macrophages. Therapeutic tactics for celiac disease today include a gluten-free diet, which is not so easy to follow. Of interest is the study of the possibility of using polyphenols in celiac disease, which are capable of precipitating gliadins and inhibiting the polarization of macrophages towards a proinflammatory phenotype, while simultaneously stimulating an increase in the population of macrophages of an anti-inflammatory phenotype associated with a decrease in tissue damage.Conclusion. Impaired macrophage function/differentiation results in either inadequate, excessive immune activation or failure to mount effective protective immune responses against pathogens, which may result in the development of gastrointestinal diseases. Studying the involvement of macrophages at different stages of celiac disease progression is important for the development of new treatments for this disease.